Pengaruh Kompetensi dan Disiplin Kerja terhadap Kinerja Dosen Program Studi Sarjana Akuntansi Universitas Pamulang - Sadewa, Prima; Damayanti, Riska; Sopiyana, Muhammad (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Improving lecturer performance is essential for ensuring the quality of higher education, particularly in responding to the growing demands of academic excellence and institutional accountability. This research aims to examine the influence of two critical factors competence and work discipline on lecturer performance. Specifically, the objectives are: (1) to determine the influence of competence on lecturer performance, (2) to determine the influence of work discipline on lecturer performance, and (3) to determine the simultaneous effect of competence and work discipline on lecturer performance. This study employs a quantitative approach and is classified as associative research. The research was conducted in the Accounting Study Program at Pamulang University. The population consisted of 145 lecturers, and the sample was selected using convenience sampling. Data were collected through questionnaires and analyzed using data quality testing, classical assumption testing, regression analysis, and hypothesis testing. The results indicate that both competence and work discipline significantly affect lecturer performance, both individually and simultaneously. Competence contributes to lecturers' ability to perform academic tasks effectively, while work discipline improves consistency and responsibility. The combined influence of both factors shows a stronger positive impact on performance. These findings highlight the importance for higher education institutions to enhance lecturer competence through training and foster a disciplined academic environment.